Anxiety, depression, and their association with unintentional injury risk among older adult populations in Guangxi, China: a cross-sectional study - Niu, Li; Zhang, Jie; Lu, Chun-liu; Zhang, Yong; Mo, Xin-xin; Xu, Rong; Luo, Hong-ye (Frontiers in Public Health, 2025)
BackgroundThe aging population presents a significant public health challenge, particularly concerning mental health and injury prevention. Anxiety and depression are common among the older adult, affecting their quality of life and increasing the risk of unintentional injuries (UI). This study aims to explore the association between anxiety and depression and UI risk among the older adult in Guangxi, China, using data from the 2023 National Health Service Survey.MethodsA cross-sectional design was employed, analyzing data from 2,894 participants aged 60 and above in Guangxi. The primary variables were anxiety and depression, assessed via validated scales, with UI as the dependent variable. Logistic regression was used to estimate crude and adjusted odds ratios (OR) with 95% confidence intervals (CI), adjusting for potential confounders such as age, gender, socioeconomic status, and lifestyle factors.ResultsSignificant findings indicate that individuals with anxiety and depression had nearly double the risk of UI compared to those without these conditions (adj. OR = 1.92, 95% CI: 1.42–2.6, p < 0.001). Alcohol consumption was also associated with higher UI risk (adj. OR = 1.46, 95% CI: 1.05–2.03, p = 0.023). Females had a significantly higher adjusted odds of UI compared to males (adj. OR = 1.38, 95% CI: 1.03–1.84, p = 0.029), and rural residents were more likely to experience UI than urban dwellers (adj. OR = 1.38, 95% CI: 1.05–1.82, p = 0.02). Exercise frequency was inversely related to UI risk, with those exercising 1–2 times per week having reduced odds (adj. OR = 0.46, 95% CI: 0.22–0.98, p = 0.044). Other factors such as age, marital status, hypertension, diabetes, and main caregiver showed no significant associations with UI.ConclusionAddressing mental health issues and promoting moderate exercise may help reduce UI risk in the older adult. Policies should focus on enhancing mental health services and injury prevention programs, particularly in rural settings, to improve the overall health and safety of the aging population in Guangxi.